THE OVERVIEW OF SUBJECTIVE WELL-BEING IN GEN Z WHO HAVE WORKAHOLIC PARENTS (PSYCHOLOGY AND MENTAL HEALTH) - Huda, Fanny Sabillah; Affandi, Ghozali Rusyid (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective:  The young generation in the current era is commonly known as generation Z or Gen-Z. Gen-Z was born between 1997 and 2012. Workaholics or workaholics are people who work excessively so that they exceed the time, physical and mental limits which ultimately have to sacrifice the balance of life by neglecting rest, prayer and socialising with the people around them. subjective well-being is a person's perspective on his life, which consists of cognitive and affective assessments of his life and represents psychological well-being. Method: This research uses qualitative research methods with a phenomenological approach. The subjects of this research were selected using purposive sampling technique and the aspects that will be examined in this research are (1) Cognitive aspects in the form of satisfaction (2) Positive affective aspects (3) Negative affective aspects. Results: The results showed that subject PP and subject VA both have parents who are workaholic but these two subjects have different adaptations of subjective well-being. From the 3 aspects studied, PP tends to have adaptation of subjective well-being in his life in general and has long-term fears. On the other hand, VA has adapted subjective well-being that focuses on his personal achievements, social relationships, and has short-term fears. Novelty: The results showed that subject PP and subject VA both have parents who are workaholic but these two subjects have different adaptations of subjective well-being.